PART 1 - Ntoumanis, Laura; Wolters, Corinna; Heger, Gesine; Keil, Anja; Sanfilippo-Schulz, Jessica; Türlings, Svea; Ziejewski, Anja; Neumann, Dorit; Preusser, Alisa (Satura, 2018)
Complementary opposites, as seen Dating Gulliver Atrax Carnivore Train Ride Driftwood Just Kidding Newspaper Clipping